Comparative Study Between Internal Ohmic Resistance and Capacity for Battery State of Health Estimation - M. Nisvo Ramadan; Bhisma Adji Pramana; Sigit Agung Widayat; Lora Khaula Amifia; Adha Cahyadi; Oyas Wahyunggoro (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
In order to avoid battery failure, a battery management system (BMS) is necessary. Battery state of charge (SOC) and state of health (SOH) are part of information provided by a BMS. This research analyzes methods to estimate SOH based lithium polymer battery on change of its internal resistance and its capacity. Recursive least square (RLS) algorithm was used to estimate internal ohmic resistance while coloumb counting was used to predict the change in the battery capacity. For the estimation algorithm, the battery terminal voltage and current are set as the input variables. Some tests including static capacity test, pulse test, pulse variation test and before charge-discharge test have been conducted to obtain the required data. After comparing the two methods, the obtained results show that SOH estimation based on coloumb counting provides better accuracy than SOH estimation based on internal ohmic resistance. However, the SOH estimation based on internal ohmic resistance is faster and more reliable for real application